A Distributed Brillouin Optical Sensor Simulation for Measuring Stress and Temperature [Simulación de Un Sensor Óptico de Brillouin Distribuido Para Mediciones de Esfuerzos y Temperaturas] - Fernandez-Beltran, M; Valencia-Cordero, C (Institute of Electrical and Electronics Engineers Inc., 2016)
The distributed Brillouin optical sensor allows monitoring physical parameters such as temperature and stress, making them ideal for application in structural monitoring. Currently, the researches focus on improving the detection distance and resolution of these sensors, the laboratory tests are the main tools to checking the results of different theorical proposals. Therefore, the aim of this paper is to present a simulation tool of the distributed Brillouin optical sensors based on Brillouin optical frequency domain analysis since to our knowledge there is no tool that allows the simulation. For this, a simplified model of the transfer function in the Brillouin frequency domain is proposed, from which an expression for the Brillouin distributed sensor depending on the distance is obtained. The latter expression is used to perform the simulation both of the amplitude as the distance and later the behavior is verified. This simulation could be applied to other schemes based on BOFDA technique for validating sensor operation. © 2016 IEEE.